Une analyse de la souffrance enseignante : Horkheimer, Adorno et l'humain comme être souffrant - Arianne Robichaud; Marie-Hélène
This article aims to understand the phenomenon of teaching difficulties and suffering from a theoretical point of view, through the sociological and philosophical perspectives of Frankfurt School's first generation theorists Max Horkheimer and Theodor Adorno. Its main goal is to highlight the possible relation between the microsociological manifestations of suffering experienced in teaching work (adaptation problems, stress, disenchantment vis-à-vis the profession, professional and personal identity changes) and the concept of the instrumental rationalization of the educational systems. What are the possible impacts of this process of rationalization, central to Horkheimer and Adorno's theories, on the different manifestations of teacher suffering? More specifically, how does the concept of suffering in the two philosopher's theories allow us to better comprehend the difficulties facing teachers in their work? These are some of the questions that this article aims to answer.